Determination Of Consumer Surplus Using Poisson Models Through The Travel Cost Method. Case: Lizas-Ilo Well Beaches (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Natural resources and environmental services are public goods characterized by being generators of direct utility without the existence of a market in which the respective prices are formed. The research was conducted on the beaches of Pozo de Lizas de Ilo, where the individual travel cost method was applied, using the Poisson model and the Limdep 8.0 software. The surveys reveal that the number of visits is once (88%); the average monthly income was S/. 2581.84; in terms of environmental perception, 79% stated that there is no contamination; the family size is 3.38 individuals; in terms of educational level, 67% stated that they had higher education, and 66.7% were male; and the average cost of a visit was S/.1532.06 soles. The variables of cost of visit, age and family size have negative signs, which indicates an inverse relationship. However, the variables educational level, gender, monthly income and environmental perception, with positive signs, indicate a direct relationship with respect to the number of visits. Monthly income with probability P = 0.0006, which with respect to P ≤ 0.01 indicates that there is high statistical significance (z = 3.42), indicating that the higher the family income, the higher the probability of visiting the beach. The goodness-of-fit was r2 = 64.44%, with a good degree of association between variables. The minimum consumer surplus was S/.55.83 soles and the average surplus was S/. 91.32 soles and the aggregate surpluses were S/913200.00 and S/.558300.00 soles ($.164205.88 and $.268588.24). The values obtained would be voluntary contributions from visitors, so that the local authorities responsible could use the estimated amount for the conservation of environmental goods and services of the Pozo de Lizas beach.